Implementing the Poznan Strategic and Long-term Programs on Technology Transfer - Global Environment Facility (Washington, DC, 2014)
Promoting the transfer of environmentally sound technologies (ESTs) and best practices to developing and transition countries is a key priority for all countries that seek to mitigate climate change impacts and build resilience. The Global Environment Facility (GEF) is one of the entities entrusted to provide financial resources to assist developing and transition countries in implementing the United Nations Framework Convention on Climate Change (UNFCCC). The GEF launched the Poznan Strategic Program on Technology Transfer in 2008. This program supports the following activities: 1) conduct technology needs assessments; 2) support pilot priority technology projects linked to technology needs assessments; and 3) disseminate GEF experience and successfully demonstrated ESTs. The Long-Term Program on Technology Transfer seeks to scale up technology transfer activities supported under the original Poznan Program. This long-term program includes the following elements: (i) support for climate technology centers and a climate technology network; (ii) piloting priority technology projects to foster innovation and investments; (iii) public-private partnership for technology transfer; (iv) technology needs assessments; and (v) GEF as a catalytic supporting institution for technology transfer. This document provides an overview of the GEF's approach on promoting technology transfer, with new insights, along with updates on the original Poznan Program and the Long-Term Program.